Impact of breakthrough trials on prescription trends of sodium‐glucose cotransporter‐2 inhibitors in Japan: An interrupted time‐series analysis. (6th September 2022) - Iketani, Ryo; Imai, Shinobu
Abstract: What is Known and Objective: Sodium‐glucose cotransporter‐2 inhibitors (SGLT‐2is) have been increasingly prescribed for the treatment of type 2 diabetes mellitus (T2DM). We aimed to investigate the impact of clinical trials presenting remarkable results on the prescription of SGLT‐2is and the relationship between the impact and generalisability of the breakthrough trials on SGLT‐2is. Methods: This retrospective cohort study involved 32, 949 patients with T2DM who were prescribed at least one antidiabetic agent in the Japan Medical Data Center health insurance database. Prescription rates of SGLT‐2is were calculated monthly from April 2014 to March 2020. We evaluated the impact of the EMPA‐REG OUTCOME study for an Asian subgroup on the prescription rate of empagliflozin and the impact of the CANVAS/CANVAS‐R study on the prescription rate of canagliflozin. Incidence rate ratios (IRRs) and 95% confidence intervals (CIs) were estimated using the quasi‐Poisson regression model in the overall population, subgroup with a history of cardiovascular disease (high‐risk group), and subgroup without a history and risk factors of cardiovascular disease (low‐risk group). Results and Discussion: The EMPA‐REG OUTCOME study for the Asian subgroup led to increased prescription rates of empagliflozin 3 months after its publication in the overall population and high‐risk group but not in low‐risk group (IRR [95% CI]: 1.40 [1.17–1.66], 1.39 [1.05–1.84], and 1.00 [0.79–1.27], respectively). The increase in high‐risk group may be appropriate because this study included patients with a history of cardiovascular disease only. The CANVAS/CANVAS‐R study led to increased prescription rates of canagliflozin 3 months after its publication in the overall population, high‐risk group, and low‐risk group (IRR [95% CI]: 1.52 [1.06–2.19], 1.39 [1.06–1.83], and 1.81 [1.20–2.75], respectively). The increase in low‐risk group may not be appropriate because this study did not include patients without a history or risk factors of cardiovascular disease. What is New and Conclusion: The breakthrough trials increased prescription rates not only for patients to whom the trial results could be extrapolated but also for those in whom trial benefits were not certain. Our findings suggest that information about breakthrough trials may need to be provided along with data on trial result generalisability. Abstract : We aimed to investigate the impact of clinical trials presenting remarkable results on the prescription of SGLT‐2is and the relationship between the impact and generalisability of the breakthrough trials on SGLT‐2is. The EMPA‐REG OUTCOME study for the Asian subgroup, which included patients with a history of cardiovascular disease only, led to increased prescription rates of empagliflozin 3 months after its publication in the overall population and population with a history of cardiovascular disease but not in population without a history and risk factors of cardiovascular disease (IRR [95% CI]: 1.40 [1.17–1.66], 1.39 [1.05–1.84], and 1.00 [0.79–1.27], respectively). The CANVAS/CANVAS‐R study, which included patients with a history or risk factors of cardiovascular disease, led to increased prescription rates of canagliflozin 3 months after its publication in the overall population, population with a history of cardiovascular disease, and population without a history and risk factors of cardiovascular disease (IRR [95% CI]: 1.52 [1.06–2.19], 1.39 [1.06–1.83], and 1.81 [1.20–2.75], respectively). The breakthrough trials increased prescription rates not only for patients to whom the trial results could be extrapolated but also for those in whom trial benefits were not certain. Our findings suggest that information about breakthrough trials may need to be provided along with data on trial result generalisability.